2020
DOI: 10.1038/s41598-020-72041-3
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoids disrupt circadian rhythms and sleep in honey bees

Abstract: Honey bees are critical pollinators in ecosystems and agriculture, but their numbers have significantly declined. Declines in pollinator populations are thought to be due to multiple factors including habitat loss, climate change, increased vulnerability to disease and parasites, and pesticide use. Neonicotinoid pesticides are agonists of insect nicotinic cholinergic receptors, and sub-lethal exposures are linked to reduced honey bee hive survival. Honey bees are highly dependent on circadian clocks to regulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
(66 reference statements)
5
23
0
Order By: Relevance
“…The high degree of structural and functional conservation of nAChRs between flies and bees 9 , 50 , 65 , and the conserved lethal and sub-lethal effects of reduced viability, longevity, locomotion, memory, circadian rhythmicity and sleep we show in flies and as reported in bees suggests that the modes of action identified here may also occur in bees 1 , 21 , 23 , 33 , 53 56 . Previous work has shown that sub-lethal effects observed in the lab translate to the field, for example neonicotinoid reduced foraging motivation is observed in bumblebees in the lab as well as in free flying colonies in the field 20 , 66 .…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The high degree of structural and functional conservation of nAChRs between flies and bees 9 , 50 , 65 , and the conserved lethal and sub-lethal effects of reduced viability, longevity, locomotion, memory, circadian rhythmicity and sleep we show in flies and as reported in bees suggests that the modes of action identified here may also occur in bees 1 , 21 , 23 , 33 , 53 56 . Previous work has shown that sub-lethal effects observed in the lab translate to the field, for example neonicotinoid reduced foraging motivation is observed in bumblebees in the lab as well as in free flying colonies in the field 20 , 66 .…”
Section: Discussionsupporting
confidence: 65%
“…Previous work has shown that sub-lethal effects observed in the lab translate to the field, for example neonicotinoid reduced foraging motivation is observed in bumblebees in the lab as well as in free flying colonies in the field 20 , 66 . Reduced behavioural rhythmicity, shown in honeybees 23 , 33 , bumblebees 21 and here in fruit flies, is likely to reduce the amount of activity carried out in the daytime, reducing pollination and foraging opportunities 67 . The reduction in total sleep and fragmentation of sleep will reduce the quantity of deep sleep achieved, as deep sleep occurs later into the sleep episode 68 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar sensitivities to the different neonicotinoids are seen in Drosophila with the nonbanned thiacloprid being less toxic (Tasman et al, 2020(Tasman et al, , 2021. Furthermore the insecticides seem to act through a similar neuronal mechanism of action, causing initial hyperexcitability of neurons when applied to fly clock neurons in the whole brain (Tackenberg et al, 2020).…”
Section: The Introduction Of the "New Nicotine-like" Insecticides Calmentioning
confidence: 78%